ANALISIS KONDUKTIVITAS PANAS PADA MATERIAL ALTERNATIF SEBAGAI INSULASI DINDING RUANG AKOMODASI KAPAL BERBASIS LIMBAH AMPAS TEBU DAN SERBUK KAYU - Aurista Miftahatul Ilmah Aurista (Prodi Fisika FST UNJA, 2020)
The accommodation room on the ship is used as a resting place for the crew and as a storage place for goods on the ship so insulation is needed in each room to withstand the heat propagation on the ship. One type of insulation material on a ship is mineral wool which is made from polyurethane. Polyurethane is a plastic foam that is a mixture of polyol and isocynate and one of the ingredients is polymer which can be obtained from natural materials that contain lots of cellulose such as bagasse and sawdust. the addition of sawdust and bagasse that can be done is 40% of the total volume of the mixture. Then it is carried out to get the thermal conductivity value of each mixture of sawdust, bagasse, and polyurethane with various dosing ratios on the sawdust, to further calculate the cooling load. The test results show the best conductivity value is the mixing of wood powder 0.2 gr which is 2.65 w / mk which can withstand the rate of heat up to 311.59 KW.